CHEMICAL COMPOSITION AND CHARACTERISTIC OF CARAPACE FLOUR OF VANNAME SHRIMP (Litopenaeus vannamei) - Muslihul Makrif; Mirna Ilza; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT            This study aim to proportion value and chemical composition of the vanname shrimp carapace flour. The research method consisted of two stages, namely: 1) Preparation of vanname shrimp carapace flour, 2) Chemical composition analysis of vanname shrimp carapace flour. The observed parameters consisted of morphology, proportion, and chemical composition of vanname shrimp carapace flour. The result showed that vanname shrimp measuring 16 cm and weight 19.4 g and had a proportion value of 56.77% meat, carapace 35.83%, and viscera 7.39%. Chemical composition of vanname shrimp carapace flour was water content 10.07 ± 0.002% (wb), ash content 30.49 ± 0.25% (db), protein content 38.84 ± 0.01% (db), fat content 1.06 ± 0.72% (db), and carbohydrates content (by different) 29.60 ± 0.35% (db).Keywords: Vanname shrimp, Carapace, Proportion.